Novice Teachers and Native-Speakerism: Identity Recognition on Teacher for English as An International Language - Intan Pratidina Dewi; Ahmad Bukhori Muslim; Dadang Sudana (Yayasan Visi Intan Permata, 2021)
The study aims to explore three novice teachers' perception towards English native-speakerism for the exploration of English as an International Language (EIL). The concern towards English native-speakerism, preferring the English variations from its native background, in the practice of teaching English as a Foreign Language (EFL) has become the central issue, especially in Indonesia. It is not aligned with the idea of EIL which foster the process of producing competent users of English through the inclusion of local cultural-based items. The case study design will be utilized in the research using the pre-interview, document analysis, and post-interview as the instrument for data collection of novice teachers' perception of local and nativized exposure. The study discovers that all collaborated novice teachers set an agreement to support the local cultural-based inclusion in practice yet support the inclusion of standardized English for teaching pattern and pronunciation. The findings show how the teachers have acknowledged the inclusion of local exposure to maximize the endeavor for students to be competent users of English. The discussion still relies on making the local cultural-based items in teaching practices viable and proposes Englishes in the teaching to lessen the native-speakerism.